The Relationship Organizational Culture, Motivation, Resilience and Leadership of Principals with the Work Ethic of Indonesian Language Teachers - Suprapto Suprapto; Syukri Hamzah; Didi Yulistio; Susetyo Susetyo (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The article was to describes relationship between cultural organization, motivation, resilience and the leadership of headmaster with the Indonesian language teachers work ethic. It was a correlation study. The design in this study look for the relationship between four independent variables, namely organizational culture, motivation, resilience and principal leadership, with one dependent variable, namely the work ethic of the Indonesian language teacher at State Senior High School Rejang Lebong. The sample used the purpossive sampling. The data collection method used questionnaire and observation. Validity of internal questionnaire input from experts, empirical validity through trials outside the research location. Data analysis used multiple linier regression analysis. The result show that cultural organization, motivation, adversity quotient, and the leadership of headmaster have connection to work ethic the correlation coefficient was 4,841. Cultural organization has not connection to work ethic. Motivation has not connection to work ethic. Adversity quotient has not connection to work ethic; and principal’s leadershiphas not connection to work ethic. Keywords: Organizational Culture. Work Ethic, Principal Leadership